Synthesis and characterization of sol-gel bioactive glass nanoparticles doped with boron and copper. Issue 10 (15th May 2022) - Piatti, E.; Verné, E.; Miola, M.
Abstract: In this work the sol-gel synthesis of bioactive glass nanoparticles containing both boron and copper oxides is reported for the first time in the literature. Two acid/base co-catalysed methods were compared. The obtained glasses have been characterized in terms of morphology, composition, particle surface area, phase analysis and bioactivity in acellular simulated body fluids. The almost spherical nanoparticles (<100 nm diameter) obtained are characterized by a certain degree of aggregation and have compositions, which are coherent with the theoretical ones. Each glass revealed the ability to promote the growth of hydroxyapatite on its surface during soaking in simulated body fluid, thus we can assume that the addition of boron and copper did not negatively affect the bioactivity of the sol-gel derived glasses. Future investigations will be devoted to biological characterizations for cytotoxicity, antibacterial properties and pro-angiogenetic abilities.